2012
DOI: 10.1111/are.12077
|View full text |Cite
|
Sign up to set email alerts
|

The effect of poly-β-hydroxybutyrate on the performance of Chinese mitten crab (Eriocheir sinensisMilne-Edwards) zoea larvae

Abstract: This study investigated the protective effect of polyb-hydroxybutyrate (PHB) on Chinese mitten crab, Eriocheir sinensis, zoea larvae challenged with pathogenic Vibrio anguillarum. PHB was delivered to the crab larvae through rotifer and Artemia bioencapsulation. Zoea 3 larvae were challenged with V. anguillarum at a final concentration of 10 5 CFU mL )1. PHB-enriched rotifers and Artemia nauplii were added to the culture water 24 h prior to, upon and 24 h after challenge. The results confirmed that PHB could e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
17
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(18 citation statements)
references
References 21 publications
1
17
0
Order By: Relevance
“…In the current study, 1% and 3% PHB supplementation in the feed of juvenile Chinese mitten crab resulted in faster moulting and correspondingly better body weight gain. This confirms the previous observations of PHB containing diets benefiting the moulting and survival of Chinese mitten crab zoeal larvae (Sui et al 2012(Sui et al , 2014. These observations are also in accordance with the results reported on fish such as European sea bass , Siberian sturgeon (Najdegerami et al 2012), and other crustacean species such as the giant freshwater prawn (Nhan et al 2010).…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…In the current study, 1% and 3% PHB supplementation in the feed of juvenile Chinese mitten crab resulted in faster moulting and correspondingly better body weight gain. This confirms the previous observations of PHB containing diets benefiting the moulting and survival of Chinese mitten crab zoeal larvae (Sui et al 2012(Sui et al , 2014. These observations are also in accordance with the results reported on fish such as European sea bass , Siberian sturgeon (Najdegerami et al 2012), and other crustacean species such as the giant freshwater prawn (Nhan et al 2010).…”
Section: Discussionsupporting
confidence: 92%
“…This confirms the previous observations of PHB containing diets benefiting the moulting and survival of Chinese mitten crab zoeal larvae (Sui et al . , ). These observations are also in accordance with the results reported on fish such as European sea bass (De Schryver et al .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…() reported that feeding the giant freshwater prawn ( Macrobrachium rosenbergii ) larvae with poly β‐hydroxybutyrate (PHB)‐containing Artemia nauplii significantly increased survival and development of the larvae. Sui, Liu, Sun, Wille, Bossier and Schryver () reported that bio‐encapsulation of PHB into rotifers and Artemia was an efficient approach to deliver PHB to the Chinese mitten crab ( Eriocheir sinensis ) larvae and resulted in a significantly enhanced survival, development rate and osmotic tolerance. The addition of commercial PHB particles (average diameter 30 μm) or PHB‐containing bacteria protects Artemia franciscana from pathogenic Vibrio campbellii (Defoirdt, Halet, Vervaeren, Boon, Van de Wiele, Sorgeloos, Bossier & Verstraete ; Halet et al .…”
Section: Scfas and Their Salts Effects On Growth Performance And Physmentioning
confidence: 99%
“…PHB and/or its degradation product β‐HB can probably also be used as an energy source by crustaceans (Sui et al . ). Organic acids, mainly butyric acid, have also been mentioned as typical energy sources for the growth of intestinal epithelial cells (Biagi et al .…”
Section: Introductionmentioning
confidence: 97%